Where is the comfort in comfort foods? Mechanisms linking fat signaling, reward, and emotion. Issue 3 (March 2014) - Weltens, N.; Zhao, D.; Van, L.
Abstract Background Food in general, and fatty foods in particular, have obtained intrinsic reward value throughout evolution. This reward value results from an interaction between exteroceptive signals from different sensory modalities, interoceptive hunger/satiety signals from the gastrointestinal tract to the brain, as well as ongoing affective and cognitive processes. Further evidence linking food to emotions stems from folk psychology ('comfort foods') and epidemiological studies demonstrating high comorbidity rates between disorders of food intake, including obesity, and mood disorders such as depression. Purpose This review paper aims to give an overview of current knowledge on the neurophysiological mechanisms underlying the link between (fatty) foods, their reward value, and emotional responses to (anticipation of) their intake in humans. Firstly, the influence of exteroceptive sensory signals, including visual, olfactory ('anticipatory food reward'), and gustatory ('consummatory food reward'), on the encoding of reward value in the (ventral) striatum and of subjective pleasantness in the cingulate and orbitofrontal cortex will be discussed. Differences in these pathways and mechanisms between lean and obese subjects will be highlighted. Secondly, recent studies elucidating the mechanisms of purely interoceptive fatty acid‐induced signaling from the gastrointestinal tract to the brain, including the role of gut peptides, will be presented. These studies have demonstrated that such subliminal interoceptive stimuli may impact on hedonic circuits in the brain, and thereby influence the subjective and neural responses to negative emotion induction. This suggests that the effect of foods on mood may even occur independently from their exteroceptive sensory properties.